Optimizing Electoral Integrity: The Effectiveness of Bawaslu Kubu Raya's Strategies in Preventing Violations in the 2024 General Election - Larasati, Azizah; Heronimus, Viktorius; Alsina, Bima; Ramadanu, Ramadanu; Yinwana, Nursiti (Indonesian Journal of Education and Social Sciences, 2025)
Elections play a crucial role in empowering citizens to choose their leaders. Every eligible citizen has the right to vote for their preferred candidate or party, and the outcomes determine leadership at various levels of government. Bawaslu, as an election monitoring agency, holds a critical mandate to develop and implement strategies to prevent violations during the electoral process. This study aims to evaluate the effectiveness of Bawaslu Kubu Raya’s strategies in preventing violations during the 2024 elections. A qualitative descriptive research method was employed to provide an in-depth understanding of this issue. Data collection techniques included observation, interviews, and documentation, while Hasibuan’s effectiveness indicators—Work Quantity, Time Utilization, and Capacity Building—were used to assess the strategies. The findings reveal that Bawaslu Kubu Raya’s strategies are optimal, as evidenced by a reduction in reported violations and proactive community involvement in monitoring. This study underscores the importance of collaborative initiatives and capacity-building efforts in enhancing electoral integrity and transparency.